Peran program kelas ibu hamil terhadap pelaksanaan ASI eksklusif di Gunung Kidul - Dwi Andayani; Ova Emilia; Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
The influence of antenatal class implementation toward exclusive breastfeeding in Gunung Kidul Purpose This study aimed to determine the effect of the implementation of the antenatal class toward exclusive breastfeeding.Methods The research was a case-control study with a quantitative approach. This research was also supported by a qualitative approach which aimed to complement and reinforce the results obtained from the quantitative data. Sample cases were 135 exclusive breastfeeding infants aged 6-12 months, and the control sample were 135 not exclusive breastfeeding infants aged 6-12 month. Data analysis used the McNemar and conditional logistic regression tests with significance level of p = <0.05 and 95% confidence interval.Results Bivariate analysis showed that antenatal class affected exclusive breastfeeding p = 0.026 and OR = 1.80 (95% CI: 1.03 to 3.24). In the results of multivariate analysis after controlling by including support of her husband and the ANC p = 0.03 and OR = 1.86 (95% CI: 1.05 to 3.30). Mothers who attended antenatal class have exclusive breastfeeding rate 1.86 times higher compared to mothers who did not attend the antenatal class.Conclusion The antenatal class can directly affect exclusive breastfeeding, in spite of controlling the support of her husband and the ANC.